Peran Pemerintah dalam Pemberdayaan Pasar Setelah Covid-19 Guna Meningkatkan Kesejahteraan Masyarakat di MMTC Kota Medan - Ria Veronika , Elsadai; Christine Samosir, Jelita Maria; Jumay Eferta Tarigan; Kemala Dewi Lubis, Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the role of the government in post-Covid-19 market empowerment to improve community welfare in Mmtc Medan City. This research uses a qualitative approach research design with descriptive methods. The subjects in this research were UMKM bouquet sellers and cleaners at the MMTC Market. Data was collected using documentation, observation and interview methods. The analysis stages were carried out deductively with a focus on effectiveness theory as the basis for the analysis. The research results highlight the significant impact on MMTC Market MSMEs. Decreasing turnover and difficulty accessing capital are the main challenges. The government responded with various policies, including the Large-Scale Social Restrictions (PSBB) program and a Circular from the Minister of Trade.